N-of-1 randomized clinical trials - Onghena, Patrick (Henry Stewart Talks, 2007)
History and impact of N-of-1 RCTs, Distinguishing N-of-1 RCTs: case studies and time series research, The funnel approach to measurement, The randomized experimental approach, Types of N-of-1 designs and replications, How to randomize and analyze, Validity of N-of- 1 RCTs
Archived at 2018/05/31